Enhancing Teacher Professionalism in Indonesia: Challenges and Strategies for Digital Technology Utilization in the Society 5.0 Era - Masitoh, Sabingatun Dewi; Purbowati, Dwi (HEUTAGOGIA: Journal of Islamic Education, 2024)
Abstract: The Society 5.0 era presents new challenges for the world of education, especially in improving teacher professionalism in utilizing digital technology. This study aims to analyze the challenges teachers face and identify strategies that can be applied to enhance their professionalism. The research method used is the Narrative Literature Review (NLR), with a qualitative approach based on thematic analysis of various relevant literature sources. The PRISMA method is applied to ensure a systematic selection and analysis process. The study results indicate that teacher professionalism in the Society 5.0 era is influenced by five main aspects: understanding digital technology, developing 21st-century competencies, implementing a humanistic learning approach, increasing capacity through continuous learning, and collaborating with various educational stakeholders. However, teachers face multiple challenges, including adaptation to digital technology, the digital literacy gap, the complexity of teacher tasks, inequality in access to technology, and demands for continuous competency development. The implications of this study emphasize the need for a holistic approach to improving teacher professionalism, with policy support that encourages constant training and the provision of adequate digital infrastructure. With the right strategy, teachers can optimize their role in forming an adaptive, innovative, and highly competitive generation in the Society 5.0 era.   Abstrak: Era Society 5.0 menghadirkan tantangan baru bagi dunia pendidikan, terutama dalam meningkatkan profesionalisme guru dalam pemanfaatan teknologi digital. Penelitian ini bertujuan untuk menganalisis tantangan yang dihadapi guru serta mengidentifikasi strategi yang dapat diterapkan untuk meningkatkan profesionalisme mereka. Metode penelitian yang digunakan adalah Narrative Literature Review (NLR), dengan pendekatan kualitatif berbasis analisis tematik terhadap berbagai sumber literatur yang relevan. Metode PRISMA diterapkan untuk memastikan proses pemilihan dan analisis yang sistematis. Hasil penelitian menunjukkan bahwa profesionalisme guru di era Society 5.0 dipengaruhi oleh lima aspek utama: pemahaman teknologi digital, pengembangan kompetensi abad ke-21, penerapan pendekatan pembelajaran humanis, peningkatan kapasitas melalui pembelajaran berkelanjutan, serta kolaborasi dengan berbagai pemangku kepentingan dalam pendidikan. Namun, terdapat berbagai tantangan yang dihadapi guru, antara lain adaptasi terhadap teknologi digital, kesenjangan literasi digital, kompleksitas tugas guru, ketimpangan akses teknologi, dan tuntutan pengembangan kompetensi secara berkelanjutan. Implikasi dari penelitian ini menegaskan perlunya pendekatan holistik dalam peningkatan profesionalisme guru, dengan dukungan kebijakan yang mendorong pelatihan berkelanjutan serta penyediaan infrastruktur digital yang memadai. Dengan strategi yang tepat, guru dapat mengoptimalkan peran mereka dalam membentuk generasi yang adaptif, inovatif, dan berdaya saing tinggi di era Society 5.0.